A Literary Insight into Stanyajanana dashemani - Sonia Raj, S (International Research Journal of Ayurveda & Yoga, 2025)
Breast milk, regarded as the nectar of infant health, is referred to as “stanya” in Ayurveda. The growth and development of an infant are mainly dependent on stanya. The quantity and quality of breast milk reflect the mother’s overall health status. According to Acarya Caraka, stanya is considered an upadhatu of rasa, formed from the prasada bhaga of rasa dhatu. The production and secretion of stanya are closely influenced by the mother’s physical and mental well-being. According to Ayurveda, improper diet and lifestyle, along with mental disturbances, such as anger, grief, and fear in the mother, can impair lactation. Ayurveda has recognized the vital role of stanya in child’s growth and development. Classical texts elaborate not only on the formation and physiological aspects of stanya, but also on its abnormalities and their management. Acharya Caraka highlights two major concerns related to the purification and production of stanya and prescribes two sets of ten drugs, namely, stanyajanana dashemani and Stanyajanana dashemani to address these issues. Caraka classifies ten key herbs under stanyajananamahakashaya, collectively known as stanyajanana dashemani, to promote lactation. These herbs include virana, sali, shashtika, ikshuvalika, kusa, kasa, gundra, itkata, and katruna. Most of these herbs possess madhura rasa and qualities, such as snigdha, sita, guru, manda, and sandra. Due to their nourishing and cooling attributes, these drugs are also beneficial in conditions arising from rasakshaya and mutrajanya vikaras. This paper aims to highlight the significance of stanyajanana dashemani in promoting the production of breast milk